Effects of 4‐phenylbutyrate therapy in a preterm infant with cholestasis and liver fibrosis. Issue 6 (4th February 2016) - Ito, Shogo; Hayashi, Hisamitsu; Sugiura, Tokio; Ito, Koichi; Ueda, Hiroko; Togawa, Takao; Endo, Takeshi; Tanikawa, Ken; Kage, Masayoshi; Kusuhara, Hiroyuki; Saitoh, Shinji
Abstract: The bile salt export pump is expressed at the canalicular membrane of hepatocytes and mediates biliary excretion of bile salts. 4‐Phenylbutyrate (4 PB), a drug used to treat ornithine transcarbamylase deficiency, has been found to increase the hepatocanalicular expression of bile salt export pump. The beneficial effects of 4‐phenylbutyrate therapy have been reported for patients with progressive familial intrahepatic cholestasis, an inherited autosomal recessive liver disease. This is the first study to show the therapeutic effect of 4 PB in a preterm infant with cholestasis and liver fibrosis. The preterm infant had severe cholestasis with jaundice and failure to thrive refractory to ursodeoxycholic acid. Histology indicated giant cell hepatitis, cholestasis, and severe fibrosis. Bile salt export pump immunostaining showed lower expression than in a control. Oral 4 PB was started at a daily dose of 200 mg/kg/day. After the start of 4 PB therapy, cholestasis improved.